Effect of Regional Integration on Intra-Regional Informal Agricultural Trade in West Africa - Kligue, Kossi Ade; Yovo, Koffi (European Scientific Journal, ESJ, 2025)
This research analyzes the effect of regional integration on informal intra-regional agricultural trade in West Africa[1], based on an augmented gravity model, over the period 2010–2022. It assesses the significant impact of the Common External Tariff (CET) of the Economic Community of West African States (ECOWAS) and the gradual implementation of the African Continental Free Trade Area (AfCFTA) on informal agricultural trade among West African countries. The results reveal a significant correlation between these integration initiatives and a marked decline in informal agricultural trade, thereby raising crucial questions about the effective inclusion of these key actors within regional economic integration frameworks. [1] In this research, West Africa is defined as the ECOWAS countries, excluding Cape Verde.